As concepções de impactos no contexto do Núcleo de Altos Estudos Amazônicos (NAEA): percepção docente e produtos da pós graduação - Miranda, Suzanne Lais Santana (2022)
The present study originates from the trajectory, relationships and interrelationships that are developed and established within the scope of Higher Education: the dialogue of the university as an organization and its surroundings. Although we know that the study agendas on university topics and their dialogues with regional development are not necessarily recent, an aspect that, in a way, helped in the construction of the guiding thread of the present study, and differentiates them from other previous studies, says regarding the emergence in the last decades of a scenario of evaluation of Higher Education and, especially, that of Graduate Studies, which had repercussions on the constitution of elements such as accreditation, social, economic and cultural impact. Faced with such a scenario, the reflection between the impact category within the scope of Graduate Programs and in the context of interaction with organizations. The problem has as its object, the Center for Higher Amazonian Studies (NAEA), conceived from three interdependent pillars that distinguish it from the others and give it a unique character: development, interdisciplinarity and Amazon. As a general objective, it seeks to verify and analyze the impact categories on society, based on the concepts and actions developed by the Environment Center - NAEA in the context of the Stricto Sensu Post-Graduation through the Post-Graduate Program in Development of the Humid Tropic - PPGDSTU. Its interactions with organizations also considering the tensions experienced in contemporary times in the midst of Graduate Studies, its evaluation policies and guidelines from agencies and funding agencies. This is a qualitative and field research. Due to the singularity of the object, it is considered a case study. In terms of data collection, they were primarily collected through semi-structured interviews and institutional documents. The analyzes were constructed through content analysis, whose a priori categories are: a) conceptions of impact and b) interactions with organizations in the midst of regional development.